Development of Speech and Motor Processes in Children with Dysarthria - D.A.Rakhmatova (Zien Journals, 2023)
The article discusses the etiology, symptoms and mechanisms of dysarthria, as they are represented primarily in the development of speech and motor processes in children with dysarthria. It has been shown that the features of speech motor skills are caused by impaired functioning of those motor nerves that are involved in articulation
Keywords: development; speech processes; motor processes; dysarthria